2018
DOI: 10.1038/s41598-018-29703-0
|View full text |Cite
|
Sign up to set email alerts
|

Annexin A2 overexpression associates with colorectal cancer invasiveness and TGF-ß induced epithelial mesenchymal transition via Src/ANXA2/STAT3

Abstract: Annexin A2 (ANXA2) is upregulated in several malignancies, including colorectal cancer (CRC). However, there is little knowledge on the molecular mechanisms involved to its upregulation. The aim of this study was to identify the mechanism through which ANXA2 overexpression leads to CRC progression and evaluate its potential prognostic value. We used human CRC samples to analyse the correlation between ANXA2 levels and tumour staging. ANXA2 expression was increased in CRC tissues compared to normal colon tissue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
54
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(62 citation statements)
references
References 22 publications
7
54
0
Order By: Relevance
“…We have reported that pY23-Anxa2 binds to and enhances STAT3 activation and promotes invasion and metastasis of breast cancer cells [56]. Consistently, Anxa2 associates with STAT3 and confers the aggressive behavior in colorectal cancer [46,66]. Interestingly, Rack1 is also involved in the activation of STAT3 in several cancer cells [36,67].…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…We have reported that pY23-Anxa2 binds to and enhances STAT3 activation and promotes invasion and metastasis of breast cancer cells [56]. Consistently, Anxa2 associates with STAT3 and confers the aggressive behavior in colorectal cancer [46,66]. Interestingly, Rack1 is also involved in the activation of STAT3 in several cancer cells [36,67].…”
Section: Discussionmentioning
confidence: 71%
“…A high level of Anxa2 in cancer tissues is correlated with a highly aggressive phenotype [15,46,[48][49][50][51]. Increased Anxa2 expression has been shown to be specific in many drug-resistant cancer cells [2,[16][17][18][19][20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…AnxA1 induces invasiveness, drug-resistance, and generation of CSCs in prostate and pancreatic cancer by increasing the p-STAT3 level [114]. In addition, EGF/EGFR and TGF-β induce AnxA2 activation, following which p-AnxA2 directly interacts with STAT3 and subsequently enhances EMT in BC and CRC [115,116].…”
Section: Other Proteins As Orchestratorsmentioning
confidence: 99%
“…Thin (0·1 mm) Z-stacks of high-resolution image frames were collected in 5 rotations by utilizing an alpha Plan-Apochromat 63×/1·46 oil DIC M27ELYRA objective. Image acquisition, reconstruction, and alignment for structured illumination microscopy were performed using the Zeiss ZEN 2012 SP1 software (black edition, version 8.1.5.484), as previously described 62 .…”
Section: Structured Illumination Microscopy (Sr-sim)mentioning
confidence: 99%